Cover Image, Volume 1, Issue 3, July 2022. Issue 3 (20th July 2022) - Unknown
Abstract : Front Cover : A Nafion protective layer is fabricated for stabilizing lithium metal anodes in working lithium–sulfur batteries by Zhang and co‐workers. In article number 20220006, the Nafion protective layer alleviates the parasitic reactions between lithium polysulfides and lithium metal anodes.